A cosmological exclusion plot: Towards model-independent constraints on modified gravity from current and future growth rate data - Taddei, Laura; Amendola, Luca (Arxiv, 2015)
Most cosmological constraints on modified gravity are obtained assuming that the cosmic evolution was standard $Λ$CDM in the past and that the present matter density and power spectrum normalization are the same as in a $Λ$CDM model. Here we examine how the constraints change when these assumptions are lifted. We focus in particular on the parameter $Y$ (also called $G_{eff}$) that quantifies the deviation from the Poisson equation. This parameter can be estimated by comparing with the model-independent growth rate quantity